Solidaritas Sosial Masyarakat Hindu Bali Dalam Pelaksanaan Tradisi Ogoh-ogoh Di Desa Sebamban Baru - Komalasari, Anggi; An’amta, Dimas Asto Aji (CV. ITTC INDONESIA, 2024)
Ogoh-ogoh is a statue with various forms that are believed to be able to absorb negative things around humans. This study is to determine the meaning and social solidarity of the Balinese Hindu community in carrying out the Ogoh-ogoh tradition in Sebamban Baru village. The type of qualitative research with a descriptive approach. Data collection through non-participant observation, semi-structured interviews, and documentation. Data analysis using the Miles and Huberman model. The results of the study found that: (1) The meaning in the tradition is that Ogoh-ogoh is believed to be able to absorb negative spirits which are then burned to eliminate the spirits. The values ​​contained in the meaning are religious, arts and culture, social and tolerance values. (2) The social solidarity that emerges in the Balinese Hindu community in the practice of the Ogoh-ogoh tradition in Sebamban Baru village is mechanical and organic solidarity according to Emile Durkheim. Mechanical solidarity is shown by cooperation, mutual cooperation, mutual respect and non-discrimination. Organic solidarity can be seen from the division of tasks, where the tradition holders have been determined and cannot be replaced.